Global perspectives on the biodegradation of LDPE in agricultural systems - Mendoza, Jani E.; Tineo, Daniel; Chuquibala-Checan, Beimer; Atalaya-Marin, Nilton; Taboada-Mitma, Victor H.; Tafur-Culqui, Josué; Tarrillo, Ever; Gómez-Fernández, Darwin; Goñas, Malluri; Reyes-Reyes, María Andrea (Frontiers in Microbiology, 2025)
The increasing use of plastics globally has generated serious environmental and human health problems, particularly in the agricultural sector where low-density polyethylene (LDPE) and other plastics are widely used. Due to its low recycling rate and slow degradation process, LDPE is a major source of pollution. This paper addresses the problem of plastic accumulation in agriculture, focusing on LDPE biodegradation strategies. The studies reviewed include recent data and the methodologies used include state-of-the-art technologies and others that have been used for decades, to monitor and measure the degree of biodegradation that each treatment applied can have, including SEM, GCMS, HPLC, and microscopy. The countries investigating these biodegradation methodologies are identified, and while some countries have been developing them for some years, others have only begun to address this problem in recent years. The use of microorganisms such as bacteria, fungi, algae, and insect larvae that influence its decomposition is highlighted. A workflow is proposed to carry out this type of research. Despite the advances, challenges remain, such as optimizing environmental conditions to accelerate the process and the need for further research that delves into microbial interactions in various environmental contexts.